Implementation of Artificial Intelligence (AI) as a Companion Tutor in Nahwu Sharaf Learning - Ardiyan Sahabu; Santi Amin; Andi Nurmawaddah; Hamdy M. Zen; Adiyana Adam (Manunggal Halim Jaya, 2026)
This study aims to analyze the implementation of Artificial Intelligence (AI) as a supporting tutor in learning Nahwu and Sharaf for third-semester students of the Arabic Language Education Study Program (PBA) at IAIN Ternate in the 2025–2026 academic year. This study used a mixed methods approach with a sequential explanatory design, combining quantitative and qualitative data. Quantitative data were obtained through pre- and post-tests to measure learning outcome improvements, while qualitative data were collected through perception questionnaires, interviews, and learning observations. The results of the study indicate that the use of AI improves learning outcomes from moderate to high, particularly in the aspects of understanding Nahwu rules, i’rab, and Sharaf application. Qualitative findings revealed that AI plays an effective role in supporting self-directed learning, enhancing student engagement, and serving as a supplementary tutor that complements the role of the lecturer. Nevertheless, pedagogical guidance from lecturers remains necessary for conceptual and abstract materials.